"Infrastructuring" Pleasure: Montjuïc Before and After the Lights of the 1929 Barcelona International Exhibition. (November 2022) - Castro-Varela, Aurelio
Montjuïc is a long flat-topped hill overlooking the harbor of Barcelona from the southeast border of the city. From 1915 onwards, it underwent a profound transformation turning it into the site of the 1929 International Exhibition. This article revolves around this turning point, examining the aesthetic role of infrastructures in delivering pleasure on the hill before and during the dazzling, monumental display that characterized the event. The sociocultural practices at play in Montjuïc before its re-urbanization are thus recalled and considered in terms of their environmental and bodily features, utterly different from the visual journey later offered within and around the Exhibition venue. I delve into these two regimes of pleasure by theorizing their material forms as functional to and expressive of specific ways of having fun. Consequently, this enquiry concerns the ambient conditions, sensorial landscapes and architectural elements through which pleasure took shape in Montjuïc from the mid-nineteenth century to 1936.